Perception, participation and community development among youths in Niger-Delta Region of Nigeria - Chima, Nwaidu James (2013)
The major objective of this research was to find the relationship between perception, participation and community development of youth’s (CDY) programs. It focus to discover and compare the level perception, participation and community development among respondents in other to find the strength of the relationship between these variables while identifying the predictor of CD among youths. Empowerment, innovation and positive youth's development theories were used as a guide in understanding of the relationship of perception and participation to CD among youths. Sample for this research consist of 322 selected beneficiaries of shell petroleum Development Company of Nigeria (SPDC’s) micro-credit loan for youths and business development in the Niger-Delta region of Nigeria. They were selected from six local governments’ areas from the three states. The states are Rivers (Ikwerre and Port-Harcourt Municipal), Imo (Owerri and Uguta) and Delta (Aniocha South and Anioch North) respectively. Data was collected through survey questionnaire developed based on eight constructs that shaped the two independent variable of perception (Interest,motive, attitude), participation (participation and Decision-making), and CD among youths (Social, Economic and Psychological development) for the dependent variables. The questionnaire was subjected to test with 24 respondents and retest with 30 respondents in other to discover the internal consistency and correlation in the items which cronbach’s alpha result proved to be valid and reliable as all the items are above 0.60. Perception measuring scales were formed based on theory of social interest (Crandall, 1975), unified motive scale (Schonbrodt and Gerdtenberg, 2012),and attitude scale which focus on cognitive, affective and behavioral response (Shivanand and Dragicevic, 2004; Eagly and Chaiken, 1993) emerged as the baselines to draw the scale used in measuring perceptions. Participation measuring scale (Davidson, 1998; Refugee youths action group, 2010) and decision-making scale which emerged from Rochester decision-making scale (Shields, eta’l, 2005) were adopted to measure the level of participation. CD among youths was measured with each of the constructs forming a scale. Social capital development model (Narayan and Cassidy, 2001),psychological development based on cognitive assessment scale and economic development measuring indicators emerged as the scales to measure CD among youths. From the result of the descriptive analysis, there is a reinforcing moderation in the level in perception (Mean=3.64, SD=.413), participation (Mean=3.71,SD= .442) and CD among youths (Mean=3.65, SD=.371). Another analysis has shown that sex do not determine the level of perception (t= -1.025, p >0.05), participation (t=-.932, p =0.352) and CD among youths (t=-.640, p =0.278) based on the result of independent sample t-test. Correlation analysis proved that there is strong relationship between perception and CD with (r =0.338, p = 0.0001). Also, it proved that participation correlate with CD of youths program with (r=0.238, p = 0.0002). A multiple regression analysis proved that interest and participation are predictors of CD (βinterest =.142, p=0.0001) and (βparticipation = .063, p = 0.54). The research concluded interest and participation contribute about 14.2% and 6.3% as predictor of CD among youths. The implication of this finding is that upgrading CDY programs to be attractive, relevant and satisfactory can boast curiosity in the life of young people in their quest to enhance social, economic and psychological development among them. This will equally increase participation that guarantees CD among youths, thus becoming a model that need to be applied in CDY programs. Therefore, youths should be given more opportunities to lead in community development of youths programs which will give room for appropriate youth’s voice in decision-making as such opportunities will enhance integration that reduces negative perception of youths towards CDY programs.